Effectiveness of ventilation strategies in reducing the temperature in the main prayer halls of mosques in Malaysia - Rasli, Nur Baitul Izati; Ramli, Nor Azam; Ismail, Mohd Rodzi; Zainordin, Nazatul Syadia; Razman, Muhammad Rizal (Taylor's University, 2021)
Mosques may have an impressive architecture, but the lack of ventilation strategies compromises the ventilation inside mosques which leads to the high use of electrical equipment and energy (i.e., the air conditioning system) to maintain desired indoor conditions. Despite the attractive designs of mosques, their central prayer halls have uncomfortable indoor temperatures. What is the role of architectural form that contributed to the high indoor temperature within the “as-built” mosques in the tropical country of Malaysia? Hence, this study aims to evaluate the effectiveness of “as-built” ventilation strategies by assessing the effects of roof types, availability of air conditioning split units (ACSUs), window-to-wall ratio (WWR) and the percentage of opaque walls within the main prayer halls of Malaysian mosques. Data collection was conducted through monitoring 21 mosques, with different roof designs, in Penang and Malacca, Malaysia. The indoor air temperature was measured according to 1) roof design (Ottoman, pyramidal and Iran and Middle East styles), 2) mechanical ventilation (ACSUs and fans), 3) WWR and 4) the percentage of opaque walls. Results show that a) the type of mechanical ventilation system, the portion of opaque walls and WWR influence high indoor air temperatures, b) the roof design types have a less significant effect on the reduction of indoor air temperature, and c) more openings on walls and facades improve air circulation and hence significantly lower the indoor air temperature.